Nepafenac Loaded Emulgel for Controlled Ocular Delivery: In vitro and Ex vivo Characterization - Agarwal, Babita; Jagdale, Sachin; Kanakdande, Tejaswini; Shinde, Rushikesh (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Emulgel, known for their unique combination of properties from both emulsions and gels, have attracted significant interest from the pharmaceutical and cosmetic industries for their versatility and usefulness. This research aims to design and assess a novel emulgel containing nepafenac for ocular drug delivery. Materials and Methods: Extensive literature research guided the formulation. Novel emulgel formulations (F1 to F9) blended O/W emulsion with castor oil, oleic acid, linseed oil and a self-emulsifying agent i.e. poloxamer 188. The gel phase was prepared by employing pluronic F-127, HPMC K 15M alone, or in their combinations. The O/W phase was integrated into the gel phase to form the emulgel. Results: 9 nepafenac emulgel batches were formulated, with oil phase and polymer concentration variations. All batches were evaluated for emulsion and gelling properties. Batch F6 was selected as the optimized formulation as its characteristics exhibited a pH of 7.2, a refractive index of 1.356, 75.12% transmittance, a viscosity of 1892 centipoise (cP), a globule size of 224 nm and zeta potential of -24 mV that are more suitable for ocular applications. In vitro and ex vivo drug release showed controlled release for 8 hr, with no histological changes. HET CAM and rabbit ocular irritation tests indicated no irritation/toxicity upon administration. Sterility testing confirmed the absence of contamination and stability studies uphold consistent characteristics over time. Conclusion: The newly developed nepafenac emulgel holds promise for efficient ocular drug delivery with favourable physicochemical properties, sustained drug release, tissue compatibility and a robust safety profile. It presents a strong candidate for future developments in ocular therapies, potentially expanding the treatment options for ocular conditions.
Keywords: Ex vivo permeation; Nepafenac; Novel Emulgel; Ocular Drug Delivery; Ocular irritancy/ toxicity